2022
DOI: 10.3390/biomedicines10030528
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Metabolic Analysis of the Anticancer Effects of Plasma-Activated Saline in Three Tumor Animal Models

Abstract: In recent years, the emerging technology of cold atmospheric pressure plasma (CAP) has grown rapidly along with the many medical applications of cold plasma (e.g., cancer, skin disease, tissue repair, etc.). Plasma-activated liquids (e.g., culture media, water, or normal saline, previously exposed to plasma) are being studied as cancer treatments, and due to their advantages, many researchers prefer plasma-activated liquids as an alternative to CAP in the treatment of cancer. In this study, we showed that plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In addition, IHC staining showed that PAS-injected treatment reduced the number of Ki-67-positive tumour cells (Figure 4e,f), suggesting that PAS-injected treatment inhibits OTSCC growth (Qi et al, 2022).…”
Section: Hnc In Nude Mouse Modelsmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, IHC staining showed that PAS-injected treatment reduced the number of Ki-67-positive tumour cells (Figure 4e,f), suggesting that PAS-injected treatment inhibits OTSCC growth (Qi et al, 2022).…”
Section: Hnc In Nude Mouse Modelsmentioning
confidence: 91%
“…This result, obtained by comparing PAS with saline in vivo, further emphasizes antitumour properties of PAS. In addition, IHC staining showed that PAS‐injected treatment reduced the number of Ki‐67‐positive tumour cells (Figure 4e,f ), suggesting that PAS‐injected treatment inhibits OTSCC growth (Qi et al., 2022 ).…”
Section: Oral Cancer In Mouse Modelsmentioning
confidence: 91%
See 1 more Smart Citation
“…As a review by Kim et al in this Special Issue introduced, there have been many studies conducted elucidating the beneficial role of PAL for treating cancer. The research article by Kong et al described the anticancer effects of PAL using three tumor animal models [ 5 ]. In this study, saline was subjected to a treatment that used a device to generate plasma using ambient air.…”
Section: Possible Role Of Plasma-activated Liquids For Treating Cancermentioning
confidence: 99%
“…[ 30 ] A recent study by Xu et al found that the addition of plasma‐treated saline to the cell culture medium could enhance the drug sensitivity of cancer cells, thereby facilitating cancer treatment. [ 31 ] Qi et al confirmed that plasma‐activated saline could effectively depress melanoma growth, [ 32 ] and plasma‐treated phosphate‐buffered saline has been evidenced to inhibit the growth of pancreatic cancer cells. [ 33 ] At the same time, it has been shown that plasma‐treated phosphate‐buffered saline can reduce immunosuppressive protein CD47 expression, thereby accelerating the demise of cancer cells.…”
Section: Introductionmentioning
confidence: 99%